The influence of polarity in binary solvent mixtures on the conformation of bis-triazinyl-pyridine in solution - Trumm, Michael; Koke, Carsten; Maiwald, Martin M.; Skerencak-Frech, Andrej; Panak, Petra (Molecular physics, 2018)
We report a combined computational and experimental study to investigate the influence of the solvent on the electronic and molecular structure of the bis-triazinyl-pyridine (BTP) ligand. Experimental measurements and quantum-chemical calculations using geometries from molecular dynamics simulations in different solvent methanol/water mixtures reveal a change in the UV/vis absorption spectra for the investigated BTP compound. This change is investigated further using nuclear magnetic resonance (NMR) techniques, both experimental and computational, to gain insight to ligand conformation. Comparison of experimental and computational results enables the analysis of relevant BTP conformers, which cannot be accessed using experimental measurements alone. Based on this approach, we conclude that the BTP ligands change conformation with decreasing solvent polarity to maximise the lipophilic accessible surface - a concept which is transferrable to various classes of compounds.
First online: 05 Dec 2017
Gesehen am 05.06.2019
Published online: 05 Dec 2017